A Systematic Literature Review of the Intersection between Social Media and Cultural Identity: Implications for Agricultural and Environmental Communication - Catherine E. Dobbins; Fallys Masambuka-Kanchewa; Alexa J Lamm (Journal of Applied Communications, 2021)
Social media has radically changed human communication patterns, impacting how people perceive scientific information. This study sought to explore how cultural identity impacts the use of, and engagement with, social media content related to agriculture and the environment. Informed by Social Representation Theory, a systematic qualitative literature review was conducted to investigate how cultural identity impacted engagement with social media sources of agricultural and environmental information. Several studies indicated differences in social media engagement between people from different cultures. However, different definitions and perspectives on cultural identity emerged with some researchers describing culture in relation to nationality and others in terms of beliefs. In cases where culture was described in relation to beliefs, it was observed that individuals are more likely to defend beliefs central to their sense of identity when contradicted by new information. Despite the availability of several studies integrating cultural identity, environment, and social media, a gap was observed within research explicating directly the intersection between science communication, cultural identity, and social media. Additionally, differences emerged between research on social media and cultural identity within agricultural communication as compared with more general environmental communication. Due to the changing dynamics in agricultural and environmental communication proliferated through social media, scholars should place greater emphasis on research aimed at investigating the impact of social identity, social media, interaction and engagement with online communication messages. Future research should investigate how a holistic social identity impacts individuals’ perceptions of science communication messages, as no clear answer emerged within the current literature.
Keywords: cultural identity; science communication; social media; social identity; social representations theory